Multi-channel Jamming Attacks using Cognitive Radios - Sampath, A.; Hui Dai; Haitao Zheng; Zhao, B.Y. (2007 16th International Conference on Computer Communications and Networks, 2007)
To improve spectrum efficiency, future wireless devices will use cognitive radios to dynamically access spectrum. While offering great flexibility and software-reconfigurability, unsecured cognitive radios can be easily manipulated to attack legacy and future wireless networks. In this paper, we explore the feasibility and impact of cognitive radio based jamming attacks on 802.11 networks. We show that attackers can utilize cognitive radios' fast channel switching capability to amplify their jamming impact across multiple channels using a single radio. We also examine the impact of hardware channel switching delays and jamming duration on the impact of jamming.